Synthesis of oligo-α-(1→2)-4,6-dideoxy-4-formamido-d-mannopyranosides related to the A epitope of the Brucella O-polysaccharide and their use for assaying of serum immunoglobulins - Volkov, Timur M.; Tsvetkov, Yury E.; Yashunsky, Dmitry V.; Kuznetsov, Anton N.; Sclyarov, Oleg D.; Babicheva, Olesia V.; Zherdev, Dmitry O.; Mukhametova, Liliya I.; Eremin, Sergei A.; Krylov, Vadim B.; Nifantiev, Nikolay E. (Frontiers in Chemistry, 2025)
Pathogenic bacteria of the genus Brucella cause a severe threat for public health and agricultural economics. The World Health Organization considers brucellosis to be one of the most serious and also neglected zoonotic diseases. The use of traditional whole-cell brucellosis vaccines complicates the differentiation between infected and vaccinated animals (DIVA). Moreover, diagnostics based on lipopolysaccharide of Brucella are susceptible to false positive results. Structural features of Brucella O-antigens make synthetic oligosaccharides promising agents for the development of diagnostic tools and vaccines against brucellosis. Here we report the synthesis of spacer-armed di-, tri-, tetra- and penta-4,6-dideoxy-4-formamido-α-(1→2)-d-mannopyranosides which are related to the A-epitope of Brucella O-antigen. The key α-(1→2)-linked disaccharide thioglycoside donor was synthesized by employing the strategy of orthogonal glycosylation of thioglycoside acceptor with trichloroacetimidate donor. Sequential block-wise assembly yielded a series of desired compounds, which were subsequently deprotected and converted into target molecules and then into their fluorescein-labeled conjugates. The obtained conjugates were employed as tracers in a fluorescence polarization assay (FPA) to detect anti-Brucella immunoglobulins. Among the studied compounds, the trisaccharide conjugate showed the greatest difference in median FP signals between Brucella-positive and Brucella-negative sera samples making it a promising candidate for developing FP diagnostic assays. The decreased FP signal in the cases of tetra- and pentasaccharide tracers can be associated with the known “propeller-effect” due to the rotational mobility of the part bearing the fluorescent label and of the fluorescein itself and/or the enlarging of the distance between the fluorescein part and the antibody-oligosaccharide complex. This observation demonstrates the advantages of using synthetic relatively small synthetic tracers with well-defined structure in comparison with heterogeneous fluorescein-labelled O-polysaccharides which are in use today in spite of the fact that they contain poorly characterized amounts of label attached along the polysaccharide chains.